Internal Control System Analysis of the Production Cycle - Saputra, Galih; Kusuma, Indra; Hambani, Susy (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The production cycle is the core activity of a manufacturing company. Effective internal control and accounting information systems and efficiency in the production cycle are one of the strategies that can be used by the Company to stay ahead in competing with its competitors. This research aims to determine the accounting information system and internal control system implemented by the manufacturing company PT. Polyprima Cpta Superior. This research method uses descriptive research methods with qualitative research methods. The location chosen by the author is PT. Polyprima Cipta Unggul Bogor Regency is a manufacturing company engaged in plastic manufacturing and mold making. The research results found that the company's accounting information system and internal control system were very well designed, but external factors were still found that prevented the company's procedures from running well. In production planning activities, a fast reaction application is used which enters data and processes the data more quickly and the resulting information is more detailed from all parts.